2016
DOI: 10.1177/2055116916646585
|View full text |Cite
|
Sign up to set email alerts
|

Acromegaly in a non-diabetic cat

Abstract: Case summaryA 14-year-old, neutered male European shorthair cat was evaluated for a routine health check. The owner did not report any clinical signs except for respiratory stridor. On physical examination the main findings were broad facial features and increased interdental spaces. On haematology, a mild, non-regenerative anaemia was detected, whereas the serum biochemistry profile and urinalysis were unremarkable. The serum glucose concentration was within the reference interval. Serum insulin-like growth f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 17 publications
0
16
0
Order By: Relevance
“…A crucial difference between humans and cats with acromegalic cardiomyopathy is the proportion of individuals affected by DM. All cats with acromegaly in our study had DM, and only four cases of non-diabetic acromegalic cats have been reported in the literature thus far [ 32 33 ]. In contrast, DM is only reported in 15–35% of humans with HS [ 65 , 73 ].…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…A crucial difference between humans and cats with acromegalic cardiomyopathy is the proportion of individuals affected by DM. All cats with acromegaly in our study had DM, and only four cases of non-diabetic acromegalic cats have been reported in the literature thus far [ 32 33 ]. In contrast, DM is only reported in 15–35% of humans with HS [ 65 , 73 ].…”
Section: Discussionmentioning
confidence: 91%
“…Recent work indicates that 25–33% of diabetic cats have HS [ 26 , 27 ] which suggests that the disease is significantly more common in cats than in humans. Cats with HS most frequently present with signs consistent with of diabetes mellitus (DM) [ 26 31 ] although case reports of non-diabetic acromegalic cats also exist [ 32 , 33 ].…”
Section: Introductionmentioning
confidence: 99%
“…2,7 Recently, two different reports described a total of four acromegalic cats without DM. 9,10 These findings prove that, as happens in people, cats with HST can develop acromegaly without concurrent DM.…”
Section: Discussionmentioning
confidence: 56%
“…3 Only recently have cases of acromegalic cats without DM been described. 9,10 These findings highlight the importance of not overlooking acromegaly as a possible differential diagnosis in cats with compatible clinical signs, even in the absence of DM. Increased knowledge of clinical presentation in these cats could improve the diagnosis of acromegaly, thus increasing the number of acromegalic cats diagnosed before DM development.…”
Section: Introductionmentioning
confidence: 92%
“…Its diagnosis is usually suspected in cats affected by uncontrolled diabetes mellitus (DM) as a result of GH-induced insulin resistance (IR) or, secondarily, in those with neurological compromise resulting from the expansion of a pituitary tumor, and exceptionally in cats that have only typical AMG features (ScottMoncrieff, 2010;Fracassi et al, 2016). Treating IR to achieve good glycemic control becomes in most cases an essential goal in the management of AMG in cats (Scott-Moncrieff, 2010).…”
Section: Introductionmentioning
confidence: 99%